2016
DOI: 10.1016/j.bbapap.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The role of conformational flexibility in Baeyer-Villiger monooxygenase catalysis and structure

Abstract: A better understanding of the mechanistic role of the Control Loop may ultimately be helpful in designing mutants with altered specificity and improved catalytic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…These selected models were overlapped with their respective template structures for structural comparison (Figure 2A). The structural models of the putative BVMOs showed overall folds similar to those of template structures, with differences in some of the loops that connect α-helixes or β-strands, especially in the so-called “Control Loop” [27] (Figure 2A). This loop influences the active site environment and plays a critical role in enzyme structure and catalysis, mediating NADPH (Nicotinamide Adenine Dinucleotide Phosphate, hydride reduced form) binding and substrate selection [27].…”
Section: Resultsmentioning
confidence: 99%
“…These selected models were overlapped with their respective template structures for structural comparison (Figure 2A). The structural models of the putative BVMOs showed overall folds similar to those of template structures, with differences in some of the loops that connect α-helixes or β-strands, especially in the so-called “Control Loop” [27] (Figure 2A). This loop influences the active site environment and plays a critical role in enzyme structure and catalysis, mediating NADPH (Nicotinamide Adenine Dinucleotide Phosphate, hydride reduced form) binding and substrate selection [27].…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, an altered selectivity was observed with the four substrates tested [9]. This, together with small-angle X-ray scattering (SAXS) and targeted mutation studies, suggests that the control loop has a more complex role, affecting not only overall structure, but also the active site environment [10].…”
Section: Introductionmentioning
confidence: 92%
“…Mechanistically, enzyme-bound FAD is reduced by NAD(P)H, and after molecular oxygen is activated through the formation of a peroxyflavin, which then nucleophilically adds to the carbonyl group of the substrate. The reaction mechanism and structure of type I BVMOs have been extensively studied, with cyclohexanone monooxygenase (CHMO) [7][8][9][10] and phenylacetone monooxygenase (PAMO) [11][12][13] typically serving as the prototypes. Co-crystallization studies have revealed BVMOs to be highly flexible enzymes, able to undergo large domain movements during catalysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The control loop is observed to be ordered in some CHMO crystal structures but disordered in others 21,23,36 , suggesting that its flexibility varies depending on the enzyme's position in catalytic cycle. Specifically, it is hypothesized that the control loop must become rigid to hold the NADPH cofactor and cyclohexanone during the hydride transfer stages 21 . We analyzed the flexibility of the control loop through α -carbon root mean square fluctuation (RMSF), and plot the difference between CHMO DTNP (bound with NADH) and CHMO WT (bound with NADH or NADPH, respectively) ( Figure 5).…”
Section: The Effect Of Cofactor Specificity-switching Mutations On Prmentioning
confidence: 99%